Last Interglacial Hydroclimate Seasonality Reconstructed From Tropical Atlantic Corals. Issue 2 (17th February 2018) - Brocas, William M.; Felis, Thomas; Gierz, Paul; Lohmann, Gerrit; Werner, Martin; Obert, J. Christina; Scholz, Denis; Kölling, Martin; Scheffers, Sander R.
Abstract: The seasonality of hydroclimate during past periods of warmer than modern global temperatures is a critical component for understanding future climate change scenarios. Although only partially analogous to these scenarios, the last interglacial (LIG, Marine Isotope Stage 5e, ~127–117 ka) is a popular test bed. We present coral δ 18 O monthly resolved records from multiple Bonaire (southern Caribbean) fossil corals ( Diploria strigosa ) that date to between 130 and 118 ka. These records represent up to 37 years and cover a total of 105 years, offering insights into the seasonality and characteristics of LIG tropical Atlantic hydroclimate. Our coral δ 18 O records and available coral Sr/Ca‐sea surface temperature (SST) records reveal new insights into the variable relationship between the seasonality of tropical Atlantic seawater δ 18 O (δ 18 Oseawater ) and SST. Coral δ 18 O seasonality is found to covary with SST and insolation seasonality throughout the LIG, culminating in significantly higher than modern values at 124 and 126 ka. At 124 ka, we reconstruct a 2 month lead of the coral δ 18 O versus the Sr/Ca‐SST annual cycle and increased δ 18 Oseawater seasonality. A fully coupled climate model simulates a concomitant increase of southern Caribbean Sea summer precipitation and depletion of summer δ 18 Oseawater . LIG hydroclimate at Bonaire differed from today's semiarid climate with a minor rainy season during winter. Cumulatively, our coral δ 18 O, δ 18 Oseawater, and model findings indicate a mid‐LIG northward expansion of the South American Intertropical Convergence Zone into the southern Caribbean Sea, highlighting the importance of regional aspects within model and proxy reconstructions of LIG hydroclimate seasonality. Key Points: Last interglacial (LIG) coral δ 18 O records are used to reconstruct tropical Atlantic seawater δ 18 O (δ 18 Oseawater ) seasonality A 37 year mid‐ last interglacial coral detects higher than modern δ 18 Oseawater seasonality and a 2 month lead of coral δ 18 O versus Sr/Ca Mid‐ last interglacial climate model and coral findings indicate an Intertropical Convergence Zone expansion into the South Caribbean Sea